Influence of Transformational Leadership and Psychological Empowerment on Innovative Work Behaviors of Secondary School Teachers - Ibanez, Mercedes M. (8ISC Abstract Proceedings, 2022)
Innovative individuals are indispensable in the field of education, especially school teachers who engage in different teaching and learning processes. With that scenario, few studies focused on teachers and the use of both transformational leadership and psychological empowerment to innovative work behaviors. Thus, this study aimed to identify the influence of Transformational Leadership (TL) and Psychological Empowerment (PE) on the Innovative Work Behaviors (IWB) of teachers. The respondents of this descriptive-correlational research were 60 secondary schools teachers who consented to participate using convenience sampling from four selected schools in the Philippines and one school in Micronesia. Results revealed that among the five dimensions of transformational leadership, charisma and individual attention are perceived as very highly practiced by their school heads, while psychological empowerment of the secondary school teacher was high, and meaning as one of the four dimensions of psychological empowerment was rated very high. The innovative work behavior of the secondary school teachers is high as well as its dimensions. School heads’ transformational leadership and teachers’ psychological empowerment have a direct and significant influence on teachers’ innovative work behaviors. These results will help administrators to lead and manage their respective schools by utilizing different techniques and approaches to create innovation in teachers' work behavior. Other factors may be considered to enhance the innovative work behaviors of the teachers and use qualitative research for future research. Keywords : innovative work behaviors, psychological empowerment, transformational leadership, secondary school teachers